03.07 Serum and synovial concentration of il-17a in rheumatoid arthritis patients. (1st March 2017) - Shumnalieva, Russka; Velikova, Tsvetelina; Kachakova, Darina; Monov, Simeon; Tumangelova-Yuzeir, Kalina; Kyurkchiev, Dobroslav; Rashkov, Rasho
Abstract : Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease with autoimmune character in which Th1 and T17 cells are thought to play an important pathogenic role. Th17 cells selectively produce the signature cytokines such as IL-17, IL-21 and IL-22, involved in the chronic inflammatory response and subsequent tissue damage in the affected joints in RA. Objective: The aim of our study was to compare the systemic and local concentrations of IL-17A in RA and osteoarthritis (OA) patients and to establish a possible systemic and local biomarker for RA disease activity and severity. Material and methods: Concentrations of IL-17A were compared between matched serum and synovial fluid (SF) samples from 20 RA and 15 OA patients by using Human IL-17A ELISA kit. 16 healthy donors were used as controls. Results: Levels of IL-17A were higher in RA SF compared to serum (8.645 pg/ml versus 0.315 pg/ml, p=0.012). Serum levels of IL-17A were higher in RA patients with mild compared to patients with moderate (p=0.028) and severe disease activity (p=0.069) determined by the disease activity index (DAS) 28. Regarding the simplified disease activity index (SDAI) we obtained similar results - higher serum IL-17A levels were detected in patients with mild compared to moderate (p=0.008) and to severe disease activity (p=0.037). Serum levels of IL-17A correlated negatively with the presence of anaemia (r=−0.532, p=0.016) and SF levels of IL-17A correlated with the number of swelling joints (r=0.549, p=0.012). The ROC curve analysis for IL-17A in SF showed area under the curve (AUC)=0.885 (95% CI: 0.775÷0.995), p=0.000. There was no significant difference in the serum IL-17A concentration between patients with RA and OA and compared to healthy controls (p>0.05). Conclusion: The difference between the systemic and local concentration of IL-17A shows that the local inflammatory milieu stimulates the production of IL-17A and the latter may play an important role in the disease activity and progression. Serum concentrations of IL-17A could be used as possible systemic biomarker for disease activity even in patients with mild disease activity scores or subclinical synovitis. However larger sets are needed to confirm the diagnostic and prognostic accuracy of IL-17A in RA. Acknowledgement: The study was supported by Grant 61/2015 from Medical University-Sofia, Bulgaria.